Alternative sports and their influence on the students’ motivation: An experience in Secondary Education - Menescardi, Cristina; Villarrasa-Sapiña, Israel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The aim of this study was to compare the students’ motivation after practicing alternative (AS) and traditional sports (TS) and to know the teachers’ opinion regarding this experience. From the results, it stands out that, in the AS group, in- trinsic motivation increases and extrinsic motivation decreases, while the identified motivation in the TS decreases. Teachers positively valued the experience as active, dynamic, inclusive and motivating. Physical Education teachers should consider including AS in their programs given the significant increase in intrinsic motivation towards the subject by students and the opinions and benefits highlighted by parti- cipating teachers.